2022
DOI: 10.21926/cr.2204040
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Additives on the Structure and Activity of β-Galactosidase Immobilized on a Concanavalin A–Modified Silica-Coated Titanium Dioxide Nanocomposite

Abstract: Interpreting the relationship between the activity and structure of β-galactosidase is necessary to perceive the impact of the enzyme’s conformation on its catalysis. The current study thoroughly explains the effects of additives such as ethylenediaminetetraacetic acid (EDTA), sodium dodecyl sulfate (SDS), dithiothreitol (DTT), and urea on β-galactosidase activity and structure. β-Galactosidase activity was determined at various ionic strengths and temperatures as a function of time. Structural studies evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…The K m and V max of A. oryzae β-GLs were also reduced after the covalent linking to GA-copper gelled 28 . Moreover, reduction in K m was also observed after the adsorption of A. oryzae β-GL onto graphene-iron-oxide nano-composites 43 and onto concanavalin A-layered-silica-coated titanium-dioxide 35 . The reduction in K m implied that the β-GL affinity for its substrate increased.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…The K m and V max of A. oryzae β-GLs were also reduced after the covalent linking to GA-copper gelled 28 . Moreover, reduction in K m was also observed after the adsorption of A. oryzae β-GL onto graphene-iron-oxide nano-composites 43 and onto concanavalin A-layered-silica-coated titanium-dioxide 35 . The reduction in K m implied that the β-GL affinity for its substrate increased.…”
Section: Resultsmentioning
confidence: 92%
“…The β-GL temperature optimum was not affected by its immobilization via the GA-PP-Carr beads. Analogously, the A. oryzae β-GLs temperature optima were unaltered following the covalent binding to GA-whey protein isolate grafted Carr beads 22 and the bio-affinity adsorption onto concanavalin A-layered-silica-coated titanium-dioxide 35 . Moreover, the β-glucosidase-Zn 3 (PO 4 ) 2 hybrid nanoflower and its free compeer manifested similar temperature optima 36 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the β‐galactosidase immobilised on glutaraldehyde activated SiO 2 NPs retained 87% of original enzyme activity after exposure to 35 °C for 12 h. However, the free enzyme lost its activity completely within 10 h incubation time (Verma et al ., 2012). Shafi & Husain (2022) reported that β‐galactosidase immobilised on concanavalin‐A modified silica‐coated titanium dioxide nanoparticles showed better thermal stability than free enzyme. Contradictorily, Beniwal et al .…”
Section: Resultsmentioning
confidence: 99%
“…The study also reported a shift in the optimum pH from 6.5 to 7. Verma et al (2012) and Shafi & Husain (2022) also reported a shift in the optima pH from 6.0 to 7.0 and 4.5 to 5.0 after nano-immobilisation. The nanoimmobilised enzyme retained higher activity (82.87% and 39.5%) than its free counterpart (50.26% and 8.7%) at acidic (4.5) and alkaline (8.5) pH, respectively (Selvarajan et al, 2015).…”
Section: Temperature and Ph Stabilitymentioning
confidence: 86%